Cardiovascular magnetic resonance myocardial perfusion: methods and applications in patients with coronary artery disease - Bucciarelli-Ducci, Chiara; Lyne, Jonathan C.; Gatehouse, Peter D.; Pennell, Dudley J. (SA Heart Journal, 2017)
Perfusion CMR is an attractive imaging modality that is becoming comparable with other clinically diagnostic tests. SPECT and PET are well clinically validated and have good accuracy for detection of significant CAD. However, these techniques have a rather low spatial resolution and are not suitable for the detection of subendocardial perfusion defect. In addition, the radiation burden, the potential for attenuation artefacts (SPECT) and the limited availability (PET) are limitations of these imaging techniques. An integrated assessment of myocardial perfusion, function and viability is feasible with CMR. In addition, compared to other clinically available imaging techniques, CMR perfusion has excellent spatial resolution and no ionising radiation exposure. However, it is not widely available and there is a need of protocol and pulse sequence standardization. Most perfusion analysis remains observer-dependent (“eyeball” analysis) or dependent on bolus dispersion (semi-quantitative analysis). Fully quantitative analysis using CMR perfusion is currently time-consuming for clinical application. Perfusion CMR is an evolving field with numerous future directions.